Autorzy:Praca zbiorowa
Wydawnictwo:GWO
Rok wydania:2016
Zapisz w prostszej postaci: 4.13 gwiazdek na podstawie 32 opinii

`a) \ 3sqrt{6}+ul(ul(2))-1/2sqrt{6}+ul(ul(1/2))=2 1/2+2 1/2sqrt{6}` 


`b) \ 2+root{3}{-5}+2root{3}{5}-8=ul(ul(2))-root{3}{5}+2root{3}{5}-ul(ul(8))=`  
`\ \ \ =-6+root{3}{5}` 


`c) \ ul(ul(sqrt{10}))+2sqrt{6}-ul(ul(3sqrt{10}))+sqrt{6}=3sqrt{6}-2sqrt{10}` 


`d) \ root{3}{-3}+2root{3}{9}-4root{3}{3}-5root{3}{9}=-ul(ul(root{3}{3}))+2root{3}{9}-ul(ul(4root{3}{3}))-5root{3}{9}=` 
`\ \ \ =-5root{3}{3}-3root{3}{9}` 


`e) \ sqrt{2}+2root{3}{7}+root{3}{-7}=sqrt{2}+ul(ul(2root{3}{7}))-ul(ul(root{3}{7}))=sqrt{2}+root{3}{7}`   


`f) \ 2sqrt{11}-root{3}{-11}+7root{3}{11}-sqrt{11}=2sqrt{11}+ul(ul(root{3}{11}))+ul(ul(7root{3}{11}))-sqrt{11}=` 
`\ \ \ =sqrt{11}+8root{3}{11}`